Bibliometric Analysis of Micro-teaching Model Research Trends in 2013-2023 - Jusuf Blegur; Amung Ma'mun; Agus Mahendra; I Made Sriundy Mahardika; Zuvyati Aryani Tlonaen (Yayasan Keluarga Guru Mandiri, 2023)
A comprehensive literature meta-study determines the accuracy of diagnosing past studies. It will influence plans to develop more meaningful and impactful future studies. The research aims to inspect the development of the publication of research articles on the micro-teaching model. Article data was collected using the Publish or Perish application, with the title words